IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL: PENGUJIAN DETERMINAN DAN IMPLEMENTASINYA TERHADAP AKUNTANSI BERBASIS AKRUAL - Ida Najati; Endar Pituringsih; Animah Animah (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2016)
Abstract The study objectives are to empirically examine the effects of usage of SAIBA, accounting training and organization culture on accrual accounting implementation and its implication on quality of Ministry/Board financial accounting report (LKKL). The research population are 464 SAIBA operators of KPPN Makassar I and II stakeholders. Samples which determined by slovin technique and cluster sampling are 82 respondents. Data analysis tool used is PLS with second order confirmatory factor analysis. The finding shows that accrual accounting implementation is affected by accounting training and organization culture, but it is not affected by the usage of SAIBA. The other finding indicates that accrual accounting implementation has implication on quality of LKKL.